1980
DOI: 10.1111/j.1440-169x.1980.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant of Dictyostelium Discoideum Capable of Differentiating Without Morphogenesis

Abstract: A mutant which is capable of differentiating into spores and stalk cells without forming a cell aggregate was isolated from the cellular slime mould, Dictyosteliurn discoideum. The mutant stopped developing at various stages, before formation of mature fruits, and the cells differentiated into s p o r a and stalk cells at whichever stage the develop-nent stopped. Unaggregated cells also differentiated into spores or stalk cells, depending on the culture conditions; differentiation into spores predominated in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…These results suggest that DCF is not CAMP and that the competence is acquired independently of a high concentration of CAMP. The inhibitory effect of CAMP added at an early stage of development is consistent with previous reports [13,261. Ammonia is another factor known to stimulate prespore/spore differentiation [ 1 1, 31, 36, 39, 40, 411.…”
Section: Nature Of Dcfsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that DCF is not CAMP and that the competence is acquired independently of a high concentration of CAMP. The inhibitory effect of CAMP added at an early stage of development is consistent with previous reports [13,261. Ammonia is another factor known to stimulate prespore/spore differentiation [ 1 1, 31, 36, 39, 40, 411.…”
Section: Nature Of Dcfsupporting
confidence: 92%
“…With respect to the pathway of prestalk/stalk differentiation, Kay and his coworkers [ 171 have shown that with the strain V12M2 terminal differentiation occurs even at low cell density only if cAMP and a lowmolecular-weight substance, stalk cell differentiation inducing factor (DIF), are supplied. In vitro and in vivo analysis of cAMP and DIF dependency indicates that the period during which cAMP acts precedes that of DIF, which subsequently induces prestalk and stalk characteristics [l, 14, 34, 351. Prespore/spore differentiation also requires extracellular cAMP and other cellular interactions [4,7,13,16,27,29,321, and in this case cAMP has been shown to act in later stages [26,30,331. However with respect to other interactions the time of action remains unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary experiments, at least two types of prespore-inducing substances have been found in CM. One is a heat-stable dialysable factor (M, < 5x103), which may be prespore-inducing factor (PIF) or previously reported factors [16,40,441. It appears not to be spore protein-inducing factor (SPIF), whose action can be substituted by methionine [ l 11, because 20 pA.4 methionine had no effect on differentiation in the present system.…”
Section: Discussionmentioning
confidence: 99%
“…Dictyostelium cells were grown with Escherichia coli B/r on SM agar plates (Sussman, 1951). Polysphondylium cells were grown with the same bacteria on 5-LP agar plates (0.5% lactose, 0.5% peptone; Ishida, 1980). All were allowed to develop at 21 "C in the light.…”
Section: Methodsmentioning
confidence: 99%